Relación entre estilos parentales disfuncionales e inteligencia emocional en adolescentes de instituciones educativas particulares de Lima - Bio Sam, Claudia Alessandra (2020)
The aim of the present study was to establish the relationship between the dimensions of parenting styles (abuse, overprotection and indifference) and the dimensions of emotional intelligence (intrapersonal, interpersonal, stress management, adaptability and mood). The sample consisted of 77 adolescents from 13 to 17 years who were attending private educational institutions and were not in any type of psychotherapeutic or pharmacological intervention. Measures used to assess the variables of interest included, a sociodemographic survey, the BarOn Emotional Intelligence Inventory for children and adolescents and the Measure of Parenting Styles questionnaire. Findings revealed a significant statistical correlation between the dimensions of both variables. Greater degree of abuse, overprotection or indifference were associated with diminished adolescent’s skills in the intrapersonal, stress management, adaptability and mood areas. It is concluded that parenting styles and emotional intelligence showed a significant correlation, even when parenting styles are not highly dysfunctional.